Tension Pneumocephalus after Cervical Spine Surgery: A Case Report with Review of the Literature - Maupin, Jeremiah; Burrow, Zackary; Shirazi, Cameron; Vallurupalli, Santaram (Journal of Neurological Surgery Reports, 2018)
This is the case of a 66-year-old male with cervical myelopathy secondary to severe cervical stenosis manifesting as worsening dexterity and numbness in his right hand. The patient underwent C3–C6 laminoplasty with bilateral foraminotomies. During the procedure an incidental durotomy occurred which was patched intraoperatively with Duragen and Tisseel. At 1 month follow-up, the patient reported that he was doing well and skin sutures were removed. Two days later, the patient presented to the emergency department with postoperative wound dehiscence, cerebrospinal fluid (CSF) drainage, altered mental status and lethargy. At that time, a computed tomography (CT) scan confirmed a tension pneumocephalus which was treated with a cranial burr hole and revision durotomy repair. The patient improved and was discharged to a rehabilitation facility with intact motor and cognitive function. At the 1-year follow-up appointment, he continued to do well without sequelae.
Keywords: tension pneumocephalus; dural tear; durotomy